Application of the method of SWOT-analysis as a means of strategic planning during the investigation of criminal cases in the field of economics in borders - Topchii, Vasyl Vasylovych; Zabarniy, Maksym Mykhailovych; Luhina, Nataliia Anatoliivna (Publishing House of Polonia University “Educator” and ISMA University of Applied Sciences are the co-publishers of this periodical, 2020)
A cooperation between states in criminal cases is carried out in order to achieve the goals of justice and may exist at the stage of pre-trial investigation, trial, as well as after the entry into force of a court decision (sentence, ruling). Forms of international cooperation in the investigation of criminal cases are quite diverse. The main ones are: providing legal assistance, which consists in carrying out procedural actions, because during the investigation and trial of criminal cases there is often a need to gather evidence abroad by questioning defendants, victims, witnesses, experts, conducting searches, examinations, court inspections, seizure and transfer of items, delivery, and forwarding of documents, etc.; extradition of persons for criminal prosecution or for the execution of a court sentence; arrest, search and confiscation of proceeds of crime (states undertake to cooperate in the investigation of money laundering; assist in the investigation and take appropriate measures: to freeze bank accounts, seize property to prevent its concealment; confiscate proceeds of crime or property, value of which corresponds to the value of income, etc.). The normative basis for the international cooperation in the investigation of criminal cases is the European Convention on Mutual Assistance in Criminal Matters dated April 20, 1959; the Criminal procedural code of Ukraine; Methodical recommendations of the General Prosecutor’s Office of Ukraine; Order No. 223 “On the organization of the work of the Prosecutor’s Office of Ukraine in the field of international legal cooperation” dated September 18, 2015. The legal basis for international cooperation in criminal matters is the current bilateral and multilateral international treaties of Ukraine, the binding nature of which has been approved by the Verkhovna Rada of Ukraine.Among the multilateral international agreements, there should be noted the European conventions on criminal justice: the European Convention on the Extradition with two additional protocols to it, the European Convention on Mutual Assistance in Criminal Matters with an additional protocol to it, the European Convention on the Transfer of Proceedings in Criminal Matters, The Convention on the Transfer of Sentenced Persons with an additional protocol, The European Convention on the Supervision of Conditionally Sentenced or Conditionally Released Offenders, the Convention on Laundering, Search, Seizure, and Confiscation of the Proceeds from Crime and the European Convention on the International Validity of Criminal Judgements. In addition, the Commonwealth of Independent States has the 1993 Convention on Legal Assistance and Legal Relations in Civil, Family and Criminal Matters and its 1997 Protocol; within the framework of the United Nations, there is the Convention on Transnational Crime of 2000, together with two Protocols thereto.These multilateral international agreements establish a uniform sphere of cooperation between law enforcement and judicial authorities in relation to all European countries.Today, the most effective is the method of “SWOT-analysis”, which is currently recognized in the scientific community as one of the most popular tools in strategic planning of social processes, including in the investigation of criminal cases. Although the type of analysis is still considered by most scientists as Bohomolova Ye., (2004) a method of marketing research of enterprises in the market in the context of business practice, the object of “SWOT-analysis” can be as legislation, the practice of its application and prospects of their improvement, and materials of criminal cases.Methodology. Achieving the purpose of this publication is ensured by the use of cognitive philosophical, general scientific and special methods, among which the main are analysis and synthesis, comparative law method, which allow to identify prospects for the use in criminal cases of the method of “SWOT-analysis”, which is currently recognized in the scientific community as one of the most popular tools in strategic planning of social processes. Methods of grammatical review and interpretation of legal norms have helped to identify gaps in the legislation governing the investigation of criminal cases, in particular in the field of economics, and to develop proposals for its improvement.Practical importance. International cooperation in criminal proceedings is an organizationally complex process, which requires the use of effective and efficient methods to perform the tasks of criminal proceedings, respect for the rights and freedoms of all participants in the process, including not violating a reasonable time in the investigation. To date, science has developed many methods of analyzing the law, the practice of their application, and identifying ways to improve legislation, taking into account the results of forecasting the prospects for society and the state. To ensure a high level of quality of criminal investigations in the framework of international cooperation, it is necessary to choose the one that will give the most effective results and allow to formulate the most optimal proposals in a particular criminal case and the practice of their application. An attempt to solve this problem is presented in this study.

Співпраця держав у кримінальних справах здійснюється для досягнення цілей правосуддя і може існувати на стадії досудового розслідування, судового розгляду, а також після набрання законної сили рішенням (вироком, ухвалою) суду. Форми міжнародного співробітництва при розслідуванні кримінальних справ досить різноманітні. Основними з них є: надання правової допомоги, яка полягає у здійсненні процесуальних дій, оскільки під час розслідування та судового розгляду кримінальних справ часто виникає необхідність збирання доказів за кордоном шляхом допиту обвинувачених, потерпілих, свідків, експертів, проведення обшуків, експертиз, проведення судових перевірок, перевірок, обшуків, перевірок тощо. судові огляди, вилучення та передача речей, доставка та пересилання документів тощо; видачу осіб для притягнення до кримінальної відповідальності або для виконання вироку суду; арешт, обшук і конфіскація доходів, одержаних злочинним шляхом (держави зобов’язуються співпрацювати в розслідуванні відмивання грошей; сприяють розслідуванню та вживають відповідних заходів: заморожувати банківські рахунки, накладати арешт на майно з метою запобігання його приховуванню; конфіскувати доходи, одержані злочинним шляхом, або майно, вартість з яких відповідає величині доходу тощо). Нормативною основою міжнародного співробітництва з розслідування кримінальних справ є Європейська конвенція про взаємну допомогу у кримінальних справах від 20 квітня 1959 р.; Кримінально-процесуальний кодекс України; Методичні рекомендації Генеральної прокуратури України; Наказ № 223 «Про організацію роботи прокуратури України у сфері міжнародно-правового співробітництва» від 18 вересня 2015 р. Правовою основою міжнародного співробітництва у кримінальних справах є чинні двосторонні та багатосторонні міжнародні договори України. , згода на обов’язковість яких надана Верховною Радою України. Серед багатосторонніх міжнародних договорів слід відзначити європейські конвенції з кримінального судочинства: Європейську конвенцію про видачу з двома додатковими протоколами до неї, Європейську конвенцію про Взаємна допомога у кримінальних справах з додатковим протоколом до неї, Європейська конвенція про передачу провадження у кримінальних справах, Конвенція про передачу засуджених осіб з додатковим протоколом, Європейська конвенція про нагляд за умовно засудженими або умовно звільненими. Конвенція про відмивання, пошук, вилучення та конфіскацію доходів, одержаних злочинним шляхом, і Європейська конвенція про міжнародну дійсність судових рішень у кримінальних справах. Крім того, Співдружність Незалежних Держав має Конвенцію про правову допомогу та правові відносини у цивільних, сімейних і кримінальних справах 1993 року та Протокол до неї 1997 року; в рамках ООН діє Конвенція про транснаціональну злочинність 2000 року разом із двома протоколами до неї. Ці багатосторонні міжнародні угоди встановлюють єдину сферу співпраці між правоохоронними та судовими органами по відношенню до всіх європейських країн. Сьогодні Найбільш ефективним є метод «SWOT-аналізу», який на сьогодні визнаний у науковому середовищі одним із найпопулярніших інструментів стратегічного планування суспільних процесів, у тому числі при розслідуванні кримінальних справ. Хоча вид аналізу більшість науковців все ще розглядає як метод маркетингового дослідження підприємств на ринку в контексті ділової практики Богомолова Є. (2004), об’єктом «SWOT-аналізу» може бути як законодавство, практика його застосування та перспективи їх удосконалення та матеріали кримінальних справ. Метод. Досягнення мети даної публікації забезпечується використанням пізнавально-філософських, загальнонаукових і спеціальних методів, серед яких основними є аналіз і синтез, порівняльно-правовий метод, які дозволяють виявити перспективи використання в кримінальних справах методу “ SWOT-аналіз», яка на сьогодні визнана в науковому середовищі одним із найпопулярніших інструментів стратегічного планування суспільних процесів. Методи граматичного огляду та тлумачення правових норм допомогли виявити прогалини в законодавстві, яке регулює розслідування кримінальних справ, зокрема у сфері економіки, та розробити пропозиції щодо його вдосконалення. Практичне значення. Міжнародне співробітництво у кримінальному провадженні є організаційно складним процесом, який потребує застосування дієвих та дієвих методів виконання завдань кримінального провадження, дотримання прав і свобод усіх учасників процесу, у тому числі недотримання розумних строків розслідування. На сьогодні наукою розроблено багато методів аналізу права, практики їх застосування та визначення шляхів удосконалення законодавства з урахуванням результатів прогнозування перспектив розвитку суспільства і держави. Для забезпечення високого рівня якості розслідування кримінальних справ у рамках міжнародного співробітництва необхідно вибрати таке, яке дасть найбільш ефективні результати та дозволить сформулювати найбільш оптимальні пропозиції в конкретній кримінальній справі та практиці їх застосування. Спроба вирішення цієї проблеми представлена в цьому дослідженні.
Keywords: criminal investigation; international cooperation during the investigation; application of the SWOT-analysis method; means of strategic planning during the investigation; legal regulation of international cooperation; карний розшук; міжнародна співпраця під час розслідування; застосування методу SWOT-аналізу; засоби стратегічного планування під час розслідування; правове регулювання міжнародного співробітництва